Managerial experience of nursing students: the systematization of nursing care on focus - Caroline Cechinel; Maria Eduarda Pereira Caminha; Denise Becker; Gabriela Marcellino de Melo Lanzoni; Alacoque Lorenzini Erdmann (Universidade Federal de Santa Maria, 2012)
Objective: to describe the experience of a nursing students group in Nursing Administration internship on proposing a change in the implementation process of the Nursing Care System (NCS). Method: experience Report involving three students and a professor in the seventh phase of the Undergraduate Nursing, Federal University of Santa Catarina in the first half of 2010 in a hospital ward. Results: the insertion of students in the internship field improves the experience on nursing management practice widely, making it easier to bond with the team and implement changes in NCS. Conclusions: the action required to seek resolution of the problem presented in accordance with the assumptions of the Situational Strategic Planning, the nursing process and the specifics of the unit, contributing to their training in management, aspects relevant to nursing